Treatment outcome of tuberculosis patients under directly observed treatment in Addis Ababa, Ethiopia - Belete Getahun; Gobena Ameni; Girmay Medhin; Sibhatu Biadgilign (Brazilian Journal of Infectious Diseases, 2013)
Background: Tuberculosis is one of the leading causes of mortality among infectious diseases worldwide. For effective tuberculosis control, it is a pre-requisite to detect the cases as early as possible, and to ensure that the tuberculosis patients complete their treatment and get cured. However, in many resource-constrained settings treatment outcome for tuberculosis has not been satisfactory. Objective: The aim of the study was to assess the treatment outcome of tuberculosis patients and investigate the association of demographic and clinical factors with treatment success of patients enrolled in Directly Observed Treatment Short Course program in government owned health centers over the course of five consecutive years in Addis Ababa, Ethiopia. Methods: A register based historical cohort study covering the period of July 2004 to June 2009 was conducted to determine the treatment outcome of Directly Observed Treatment Short Course in government owned health centers in Addis Ababa. Sex and age of tuberculosis patients, health center at which the patient was treated, year of treatment, type of tuberculosis for which the patient was treated, type of treatment offered to the patient, follow-up status and documented treatment outcome were extracted from the Directly Observed Treatment Short Course clinics of three randomly selected health centers. Result: Records of 6450 registered tuberculosis patients (n = 3147 males and 3433 females) were included in this document review. Of these patients 18.1% were reported as being cured, 64.6% were documented as treatment completed, 3.7% died during follow-up, 5.1% were reported as defaulters, 0.4% were documented as treatment failure and 8.2% were transferred out to another health institution. Treatment center and year of enrollment were significantly associated with treatment success. Conclusion: Year of enrollment and treatment center were significantly associated with treatment success. Although the overall treatment success obtained in this study is in line with the World Health Organization (WHO) target, continuous follow-up of patients with frequent supportive supervision during the course of treatment, and further investigate the cause for the observed difference in treatment success across treatment centers are recommended. Keywords: Treatment outcome, Tuberculosis DOTS, Ethiopia